Information Security Study for Information Hiding in Electronic Computers - H.J. Muhasin (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2005)
Cryptographic technologies are nowadays widely recognized asthe essential tool for security and trust in electronic communication. The research produces some important methods to hide information like this hide secret messages in other messages, graphic images and sound files.